Biofunctionalization of ADA-GEL Hydrogels Based on the Degree of Cross-Linking and Polymer Concentration Improves Angiogenesis - Heltmann-Meyer, Stefanie; Detsch, Rainer; Hazur, Jonas; Kling, Lasse; Pechmann, Sabrina; Kolan, Rajkumar Reddy; Osterloh, Justus; Boccaccini, Aldo R.; Christiansen, Silke; Geppert, Carol-Immanuel; Arkudas, Andreas; Horch, Raymund E.; et al. (Advanced Healthcare Materials, 2025)
The creation of bioartificial tissues is a promising option for the reconstruction of large-volume defects. The vascularization of tissue engineering constructs, as well as the material properties of the carrier matrix, are important factors for successful clinical application. In this regard, hydrogels are promising biomaterials, providing an extracellular matrix-like milieu that enables the possibility of cell transplantation and de novo tissue formation. Furthermore, biofunctionalization allows for a certain fine-tuning of angiogenic properties. This study aims to investigate vascularization and tissue formation of highly cross-linked alginate dialdehyde (ADA) and gelatin (GEL). This highly cross-linked network is created using a dural cross-linking mechanism combining ionic (Ca2+ ions) and enzymatic (human transglutaminase (hTG)) cross-linking, resulting in reduced swelling and moderate degradation rates. Vascularization of the ADA-GEL-hTG constructs is induced surgically using arteriovenous (AV) loops. Biocompatibility, tissue formation, and vascularization are analyzed by histology and X-ray microscopy. After only 2 weeks, vascularization of the ADA-GEL-hTG constructs is already present. After 4 weeks, both de novo tissue formation and vascularization of the ADA-GEL-hTG matrix increase. In conclusion, ADA-GEL-hTG-based hydrogels are shown to be promising scaffold materials for tissue engineering applications.
CRIS-Team Scopus Importer:2025-04-01
Keywords: ADA-GEL; angiogenesis; biofunctionalization; hydrogel; tissue engineering

Interdisciplinary Surgical Therapy of Extremity Soft-Tissue Sarcomas: A Personalized Resection and Reconstruction Algorithm - Osterloh, Justus; Ludolph, Ingo; Grützmann, Robert; Meyer, Alexander; Lang, Werner; Horch, Raymund E.; Fechner, Katja; Arkudas, Andreas (Journal of Personalized Medicine, 2023)
Soft-tissue sarcomas (STS) are rare, but potentially life-threatening malignancies. STS can occur anywhere in the human body with the limbs being the most common site. Referral to a specialized sarcoma center is crucial to guarantee prompt and appropriate treatment. STS treatment strategies should be discussed in an interdisciplinary tumor board to involve expertise from all available resources, including an experienced reconstructive surgeon for an optimal outcome. In many cases, extensive resection is needed to achieve R0 resection, resulting in large defects after surgery. Hence, an evaluation of whether plastic reconstruction might be required is mandatory to avoid complications due to insufficient primary wound closure. In this retrospective observational study, we present data of patients with extremity STS treated at the Sarcoma Center, University Hospital Erlangen, in 2021. We found that complications were more frequent in patients who received secondary flap reconstruction after insufficient primary wound closure compared to patients who received primary flap reconstruction. Additionally, we propose an algorithm for an interdisciplinary surgical therapy of soft-tissue sarcomas regarding resection and reconstruction and present two problematic cases to emphasize the complexity of surgical sarcoma therapy.
CRIS-Team Scopus Importer:2023-03-10
Keywords: extremity soft-tissue sarcomas; reconstructive surgery; surgical resection

In Vivo Vascularization of Cell-Supplemented Spider Silk-Based Hydrogels in the Arteriovenous Loop Model - Osterloh, Justus; Heltmann-Meyer, Stefanie; Trossmann, Vanessa T.; Cai, Aijia; Kulicke, Yvonne; Terörde, Klara; Sörgel, Celena; Lang, Isabell; Wajant, Harald; Scheibel, Thomas; Fey, Tobias; Steiner, Dominik; et al. (Biomimetics, 2025)
The goal of reconstructive surgery in treating tissue defects is to achieve a stable reconstructive outcome while minimizing donor site morbidity. As a result, tissue engineering has emerged as a key focus in the pursuit of this goal. One approach is to create a tissue container that can be preconditioned and later transplanted into the defect area. The characteristics of the matrices used in the tissue container are critical to this approach’s success. Matrices generated with recombinant, functionalized spider silk (eADF4(C16)-RGD) have been reported to be biocompatible and easy to vascularize. However, the effect of exogenously added proangiogenic cells, such as endothelial cells (T17b), on the vascularization process of matrices generated with this hydrogel in vivo has not been described yet. In this study, we implanted arteriovenous (AV) loop containers filled with a spider silk hydrogel consisting of an eADF4(C16)-RGD matrix and encapsulated, differentiated endothelial T17b cells producing the reporter protein TNFR2-Fc-Flag-GpL. The histological and µCT analyses revealed spontaneous angiogenesis and fibrovascular tissue formation in the container at 2 and 4 weeks post-implantation. The reporter protein was detected after 4 weeks. No severe immune response was observed. Altogether, this study demonstrates that cell-supplemented recombinant spider silk is a highly promising hydrogel to produce matrices for tissue engineering applications.
CRIS-Team Scopus Importer:2025-03-14
Keywords: recombinant spider silk; reconstructive surgery; tissue engineering; vascularization

Is there an impact of a video-based patient informed consent in elective hand surgery? - Osterloh, Justus; Müller-Seubert, Wibke; Cai, Aijia; Arkudas, Andreas; Horch, Raymund E. (Archives of Orthopaedic and Trauma Surgery, 2024)
Background: Patient informed consent is a crucial subject in preoperative care of patients before elective hand surgery, ensuring that patients have the necessary information and a comprehensive understanding to make autonomous decisions. The use of video-based informed consent systems is an innovative concept to enhance the consent process with multimedia tools. In addition to the conventional process, mostly relying on verbal communication and written documents, the video-based approach aims to present information in a standardized and visually appealing format. Methods: In this study, 33 patients were asked to watch a video on a tablet about the planned elective hand surgery after a conventional pre-treatment consultation including informed consent throughout verbal explanations and paper forms by an attending physician or resident. All patients were asked to complete a questionnaire after watching the video. Results: An overwhelming majority of participants, specifically 97.0%, stated that the video improved their understanding of the upcoming surgery. 90.9% of the participant would refer the video to other patients undergoing elective hand surgery, while 72.7% of participants indicated that they would have appreciated the opportunity to view an informational video before undergoing different types of surgeries in the past. Conclusion: The use of a video-based patient information system in elective hand surgery had a positive impact on patient education and satisfaction with the informed consent process. Therefore, it is a powerful tool in preoperative management to guarantee a standardized and educative informed consent.
CRIS-Team Scopus Importer:2024-06-28
Keywords: Hand surgery; Informed consent; Multimedia; Patient care

Pearls & Oy-sters: Moyamoya Vasculopathy and Its Association With Congenital Heart Disease - Osterloh, Justus; Heim, Christian; Siedler, Gabriela; Engelhorn, Tobias; Dörfler, Arnd; Schwab, Stefan; Kallmünzer, Bernd (Neurology, 2021)
CRIS-Team Scopus Importer:2021-06-25

PIK3CA mutation testing as a valuable molecular surrogate for lipomatosis of the median nerve: clinicopathological and molecular analysis of six cases - Osterloh, Justus; Agaimy, Abbas; Fried, Frederick; Stöhr, Robert; Janka, Rolf Matthias; Arkudas, Andreas; Horch, Raymund E. (Virchows Archiv, 2023)
Lipomatosis of peripheral nerves (LPN, also known as fibrolipomatous or lipofibromatous hamartoma of peripheral nerves) is a very rare, benign, intraneural, tumorous lesion that predominantly involves the median nerve but may rarely affect any peripheral nerve. Recently, PIK3CA mutations have been reported in macrodactyly, a rare condition related to LPN, and in other localized lipomatous overgrowth syndromes. In this retrospective study, we report 6 cases of FPN involving the median nerve (4 of them identified among 570 patients with carpal tunnel syndrome who underwent surgical decompression at our center from 2012 to 2022 and two seen in consultation by one of the authors). All cases were diagnosed via biopsy or resection supplemented by MRI. Patients were 4 males and 2 females aged 23 to 60 years (mean 38 years). One patient with bilateral lesions had in addition extensive angiomatosis of the paravertebral region. Histological examination showed an abnormal amount of mature fatty tissue containing disordered fibrous bands, entrapping normal-looking nerve fibers with prominent perineurial and endoneurial fibrosis. Genetic analysis using snapshot assay constructed to detect hotspots mutations in PIK3CA revealed similar PIK3CA mutations (p.H1047R; c.3140A>G) in 5/6 cases (83.3%). Our study represents a further contribution to the literature on LPN and highlights the diagnostic value of PIK3CA mutation testing as surrogate tool in equivocal cases and in those lesions without associated macrodactyly, especially as the biopsy findings of this lesion are essentially nonspecific.
CRIS-Team Scopus Importer:2023-04-28
Keywords: Everolimus; Lipomatosis; mTOR; Neuropathy; Peripheral nerves; Sequencing